Using Quinclorac to Control Annual Grasses and Palmer Amaranth in Grain Sorghum (Sorghum bicolor L.) - Grichar, James; Janak, Travis (JOURNAL OF ADVANCES IN AGRICULTURE, 2021)
Field studies were conducted during the 2015 and 2016 growing seasons in south-central Texas to determine control of Palmer amaranth and annual grasses along with grain sorghum tolerance to quinclorac alone and in various combinations when applied to weeds < 5 cm (EPOST) or 10 to 16 cm tall (LPOST). When evaluated late-season quinclorac alone at 0.43 kg ae ha-1 controlled broadleaf signalgrass 72% when applied EPOST and 91% when applied LPOST. Combinations of quinclorac with either atrazine, pyrasulfotole + bromoxynil, dicamba, or dimethenamid-P controlled Palmer amaranth 88 to 100% when applied EPOST or LPOST; however, broadleaf signalgrass control with these combination was better when applied LPOST (75 to 95%) compared with EPOST (37 to 72%) applications. Texas millet control with quinclorac was poor in both years and was never greater than 54%. Quinclorac plus either atrazine, pyrasulfotole + bromoxynil, dicamba, or atrazine + dimethenamid-P caused at least 20% sorghum injury at one of three locations. No yield reductions from the untreated check were noted in either year; however, in 2016 all treatments with the exception of quinclorac alone at 0.29 kg ha-1 applied EPOST, quinclorac + pyrasulfotole + bromoxynil applied LPOST, quinclorac + atrazine + pyrasulfotole + bromoxynil applied LPOST, and quinclorac + dicamba at either application timing produced yields that were greater than the untreated check.